Does the amount of physical activity have effect on adolescent depression and is there a gender difference? - Guðný Hrund Þórðardóttir 1975- (2014)
Physical activity has been shown to have positive effect on depression in adolescents. However, it is unclear if the amount of physical activity matters for this effect and whether there is a difference between genders. This study investigated this effect using a sample of Icelandic adolescents. The data used in this study were originally gathered in the study “Youth in Iceland 2007” (Ungt fólk á Íslandi 2007). In the current study a sample of 2000 adolescents was used for the analysis. An outpatient psychiatric rating scale, SCL-90, was used to measure each participant’s depression and the participants self-reports of weekly physical activity was used to measure physical activity. The results showed that adolescents who undertook two hours or less of physical activity per week experienced more symptoms of depression than adolescents who undertook from 3 to 9 hours, or a moderate amount, per week. However, if the amount of physical activity was greater than ten hours per week, the symptoms of depression increased again. Therefore, the conclusion is that a moderate amount of physical activity is ideal for adolescents to decrease symptoms depression.